Indonesia's Diplomacy towards UNESCO in Efforts to Inaugurate the Ciletuh-Palabuhanratu Area as a UNESCO Global Geopark - Elok Faiqoh Fajrin; Khoirunnisa Khoirunnisa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Indonesia is one of the archipelagic countries in Southeast Asia which is famous for its cultural diversity with abundant natural resources potential. One of these landscapes is Geopark or earth park. The potential of the Ciletuh-Palabuhanratu Geopark area has a value and is an important asset that must be preserved for the sake of National interest on an international scale. This study aims to explain Indonesia's diplomacy towards UNESCO in obtaining the recognition of the Ciletuh-Palabuhanratu Area as a UNESCO Global Geopark. The research method used is qualitative-descriptive using interview techniques and library research. The author uses the theory and concept of Multi-track diplomacy. Based on the results of the research obtained, it shows that there is a successful effort to involve several actors to encourage UNESCO in the inauguration of the Ciletuh-Palabuhanratu Geopark, namely through government, business, citizens, education and media channels. Finally on April 17 2018, at the UNESCO Executive Board meeting held in Paris, UNESCO inaugurated the membership status of the Ciletuh-Palabuhanratu Geopark as a Global Geopark.